Prevalence of chronic cerebrospinal venous insufficiency in multiple sclerosis: a blinded sonographic evaluation. (February 2015) - Tromba, L; Blasi, S; Vestri, A; Kiltzanidi, D; Tartaglia, F; Redler, A
Objectives: To verify the prevalence of chronic cerebrospinal venous insufficiency in patients affected by different clinical forms of multiple sclerosis and in healthy subjects using the Zamboni ultrasound protocol combined with M-mode ultrasound examination. Materials and methods: We enrolled 112 patients with multiple sclerosis and 67 healthy subjects from 20 to 67 years of age. All the patients underwent Duplex and color-Doppler sonography of the neck vessels, transcranial colour duplex sonography, M-mode study of the valve system and of venous abnormalities. Subjects were positive for chronic cerebrospinal venous insufficiency when at least two of five hemodynamic criteria of the Zamboni protocol were fulfilled. Chronic cerebrospinal venous insufficiency condition was further analyzed by a multivariate analysis including age, sex, disease duration, subtypes of multiple sclerosis and expanded disability status scale score as independent variables. Results: No healthy subjects was positive for chronic cerebrospinal venous insufficiency, while in the sample of patients affected by multiple sclerosis the diagnosis was made in 59.8% of cases ( p  < 0.0001). The first criterion was the most frequent in patients affected by multiple sclerosis and chronic cerebrospinal venous insufficiency (respectively 54.4% and 76.1%, p  < 0.001). The second, third and fourth criteria were never present in healthy subjects but were detected in patients with multiple sclerosis. The positivity of the second criterion was associated with diagnosis of chronic cerebrospinal venous insufficiency in 100% of cases. The third criterion had a prevalence of 52.2% in the subgroup of chronic cerebrospinal venous insufficiency patients. It was positive in 36 multiple sclerosis patients and was associated with chronic cerebrospinal venous insufficiency diagnosis in all cases except one. The multivariate analysis showed that age, disease duration, sex, subtypes of multiple sclerosis and expanded disability status scale score were not considered predictors of this haemodynamic condition. Conclusion: Chronic cerebrospinal venous insufficiency is a haemodynamic condition strongly associated with multiple sclerosis and is not found in normal controls. The addition of M-mode ultrasound to the diagnostic protocol allows improved observation of venous valve abnormalities.